Răspuns :
17 -12 √2 = 17 - 2 ·3· (2√2 ) = 3² - 2 · 3 ·(2√2) + ( 2√2)² = ( 3 - 2√2)²
↓ ↓
3² (2√2)² 9+4·2=17
extragem radicalul lung ⇒ I 3 -2√2I
6 - 2· 2 √2 = 4 -2√2 + 2 = 2² -2√2 +(√2)² = ( 2 - √2)² extragem radicalul lung
⇒I 2-√2I
atunci a= I 3 -2√2I - I 2 -√2 I +√2 = 3 - 2√2 -2 +√2 +√2 =3-2 =1
↓ ↓
3² (2√2)² 9+4·2=17
extragem radicalul lung ⇒ I 3 -2√2I
6 - 2· 2 √2 = 4 -2√2 + 2 = 2² -2√2 +(√2)² = ( 2 - √2)² extragem radicalul lung
⇒I 2-√2I
atunci a= I 3 -2√2I - I 2 -√2 I +√2 = 3 - 2√2 -2 +√2 +√2 =3-2 =1